2012
DOI: 10.1007/s11434-012-5193-0
|View full text |Cite
|
Sign up to set email alerts
|

Control problems in quantum systems

Abstract: The past decade or two has witnessed tremendous progress in theory and practice of quantum control technologies. Bridging different scientific disciplines ranging from fundamental particle physics to nanotechnology, the goal of quantum control has been to develop effective and efficient tools for common analysis and design, but more importantly would pave the way for future technological applications. This article briefly reviews basic quantum control theory from the perspective of modeling, analysis and desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…It should be indicated that, when the environment is initially prepared at coherent states with large photon numbers, the convolutionless model (1) is more precise than (2). However, in the case that fluctuation is comparable with the mean value, there are no much difference in precision between them.…”
Section: Nakajima-zwanzig-kernel Expansionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be indicated that, when the environment is initially prepared at coherent states with large photon numbers, the convolutionless model (1) is more precise than (2). However, in the case that fluctuation is comparable with the mean value, there are no much difference in precision between them.…”
Section: Nakajima-zwanzig-kernel Expansionmentioning
confidence: 99%
“…To resolve quantum control problems [1][2][3][4], a good mathematical model must be built up for analysis and design. From the very beginning of quantum control theory [5], semi-classical control models had been broadly used, in which the control parameters (e.g., an electromagnetic field) are taken as classical variables and the plant to be controlled is quantum.…”
Section: Introductionmentioning
confidence: 99%
“…[ 6 ] However, a major obstacle is to mitigate the problems of noise and decoherence, which lead to defects in the processing of quantum information due to the entanglement of qubits with external systems. [ 7 ] It is also important to provide simplified and efficient tools for the analysis and design of quantum control systems. Quantum control theory aims to improve these capabilities and prepare the ground for the next generation of technological applications.…”
Section: Introductionmentioning
confidence: 99%
“…The dynamics of QD and entanglement of two qubits in contact with an environment have been studied in the last decade theoretically as well as experimentally. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] It was shown that entanglement is very fragile and entanglement sudden death can occur, [6] while QD is more robust under decoherence and only presents an instantaneous disappearance at some time points in a non-Markovian regime and asymptotic decay in a Markovian regime. In particular, QD can be completely unaffected by decoherence channels for certain initial states, and this phenomenon has been observed experimentally.…”
Section: Introductionmentioning
confidence: 99%